A series of cyclopentadienyl lanthanum complexes with metalloid germanium clusters - Wörn, Kevin; Poddel'sky, Andrey; Mayer, Alex; Schrenk, Claudio; Schnepf, Andreas; Klementyeva, Svetlana V. (Inorganic chemistry, 2024)
A series of cyclopentadienyllanthanum complexes with the disilylated metalloid germanium cluster [Ge9(Hyp)2]2- [Hyp = Si(SiMe3)3] has been prepared and fully characterized. The synthetic procedure is based on the salt metathesis reaction of two different cyclopentadienyllanthanum diiodides CpLaI2 (Cp: Cp*, pentamethylcyclopentadienyl; Cpttt, 1,2,4-tri-tert-butylcyclopentadienyl) with K2[Ge9(Hyp)2] in tetrahydrofuran (THF) with a subsequent extraction with n-hexane. The composition of the obtained compounds and the mode of coordination of the germanium cluster to the rare-earth metal are strongly influenced by the steric demand of the cyclopentadienyl ligands and the crystallization conditions. The centrosymmetric dimeric compounds with the common formula [CpLa(solv)(η2,3-Ge9(Hyp)2)]2 [1, Cp = Cp*, solv-THF; 2, Cp = Cpttt, solv-NCCH2C(Me)NSiMe3] have been isolated by the slow evaporation of a n-hexane solution, while a mononuclear complex [CptttLa(THF)2(η3-Ge9(Hyp)2)] (4) was found by crystallization from THF. The repeated recrystallization of 1 from n-hexane afforded the asymmetric dimer [Cp*La(THF)(η2,3-Ge9(Hyp)2)][Cp*La(η2,3-Ge9(Hyp)2)] (3) with only one coordinated THF molecule.
Gesehen am 14.01.2025